The new English-Filipino dictionary. (Manila MECS Pub., 2004)
Intended for people who want to express their sentiments in complex or ornate Filipino words and people who are just beginning to use the Filipino Language. The book puts more emphasis on words that are frequently used today in conversations and can be read in dailies. Words that had become dormant in the vocabulary of the ordinary people were stricken out while those commonly used were given wider meaning and usage.
Keywords: English language -- Filipino. -- Dictionaries; Filipino language -- English. -- Dictionaries; Medicine -- Dictionaries